2022
DOI: 10.2196/42157
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 Lockdown Restrictions on Exercise Behavior Among People With Multiple Sclerosis Enrolled in an Exercise Trial: Qualitative Interview Study

Abstract: Background During spring and summer 2020, US states implemented COVID-19 pandemic restrictions, resulting in the closure of rehabilitation facilities and, with them, some of the clinical trials that were taking place. One such trial was the Supervised Versus Telerehabilitation Exercise Program for Multiple Sclerosis (“STEP for MS”) comparative effectiveness multiple sclerosis (MS) exercise trial. Although 1 study arm was implemented via telerehabilitation, the comparative arm took place in rehabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Our findings highlighted that many clients did not actively complete their home exercise program during lockdown, nor did they recall engaging with their exercise group leader via phone. However, other studies have found that virtually delivered programs are at least equivalent to face-to-face offerings (Jarvis et al 2022;Palmer et al 2022). This suggests that more research is also required on what facilitates client motivation and engagement in physical activity during periods of isolation.…”
Section: Discussionmentioning
confidence: 98%
“…Our findings highlighted that many clients did not actively complete their home exercise program during lockdown, nor did they recall engaging with their exercise group leader via phone. However, other studies have found that virtually delivered programs are at least equivalent to face-to-face offerings (Jarvis et al 2022;Palmer et al 2022). This suggests that more research is also required on what facilitates client motivation and engagement in physical activity during periods of isolation.…”
Section: Discussionmentioning
confidence: 98%